KAJIAN TINGKAT ALIRAN PERMUKAAN DAN EROSI, PADA BERBAGAI TIPE PENGGUNAAN LAHAN DI SUB DAS JENNEBERANG HULU - MASNANG, ANDI; SINUKABAN, NAIK; -, SUDAR (Jurnal Agroteknos, 2014)
The objective of this research was to evaluate and assess the level of run-off  and erosion on various types of land use in the Upper Jenneberang Sub Watershed. This research was conducted in the Upper Jenneberang Sub Watershed, Saluttoa Village, Sub Tinggimoncong, Gowa regency, South Sulawesi Province. Land use type (LUT) which was used as land units of observations was determined based on land use maps of upper Jenneberang sub watershed. Based on the analysis results of map and observation in the field, it was defined four types of land use as land units of observation: 1) Natural forest, 2) Gliricidia tree-dominated agroforestry, 3) Coffee tree-dominated agroforestry, and 4) Maize monoculture. Each LUT was given the observation plot size 30 m x 10 m and plot placement was determined randomly. All LUT had slope 26%, soil type of Brown Latosol at the same altitude and climate. The composition of the observation plot was based on Randomized Block Design (RBD). Collected data on LUT included: soil physical properties, infiltration rate, run-off and erosion. The result showed that changes in land use of natural forests into agroforestry and maize monoculture types resulted in decreased amount of woody vegetation that resulted in increased run-off and erosion. Keywords : run-off, erosion, agroforestry